GAME DESIGN EDUKASI PENGENALAN WISATA CIANJUR MENGGUNAKAN METODE MECHANICS DYNAMICS AESTHETICS - Muhammad Aditya Putra; Agus Komarudin; Fatan Kasyidi (Jurnal Komputasi, 2024)
The development of educational games plays a crucial role as a means to introduce interesting tourist destinations in the era of technological advancement. In this research, the development of an educational game named "Cianjur Adventure" was conducted with the aim of introducing tourist attractions in Cianjur. The development of this game utilized the Mechanic Dynamics Aesthetics (MDA) Framework. The MDA Framework consists of three main components: mechanics, dynamics, and aesthetics. Mechanics represent specific rules or algorithms that guide the interaction between players and the game. Dynamics emerge as a result of these interactions, while aesthetics encompass the responses and experiences felt by the player. To assess the performance of this game, playtesting was conducted. The results of the testing indicate that the "Cianjur Adventure" game functions well and has successfully achieved its primary goal, which is to provide information related to tourism in Cianjur. By using this game, players can experience an engaging adventure and gain deeper knowledge about tourist destinations in Cianjur.